Diagnostic Challenges of Soft Tissue Sarcomas with Special Emphasis on Immunohistochemical Profile- A Case Series - Vandana Maroo; Sanghamitra Mukherjee; Gopinath Barui; Manisha Mahata (Journal of Clinical and Diagnostic Research, 2022)
Soft tissue tumours arise from the mesenchymal tissues of different origin like adipocytic, smooth muscles, skeletal muscle, fibroblastic/myofibroblastic, fibrohistiocytic, pericytic, vascular, osteo-cartilagineous or even unknown. Its diagnosis depends on the age of the patient and site of presentation but sometimes they may present at unusual sites. Some of the tumours have overlapping histomorphological features which results in a list of differential diagnosis. Therefore, immunohistochemistry and molecular genetics play an important role for definite diagnosis. French Federation of Cancer Centres Sarcoma Group System (FNCLCC) based on necrosis, tumour grading and tumour differentiation is commonly used for grading of the sarcomas to assess the treatment response and prognosis of the patient. Hereby, authors present a series of nine cases of soft issue tumours, comprising five cases of synovial sarcomas and one each of dedifferentiated liposarcoma, rhabdomyosarcoma, epithelioid angiosarcoma and Well Differentiated Liposarcoma (WDLS). Few cases are located at unusual anatomical sites; hence, they should be kept in mind as differential diagnosis. Immunohistochemistry has played an important role for confirmation of diagnosis of synovial sarcomas and angiosarcoma.